Examining the collaborative process: collaborative governance in Malaysia - Noh, Abdillah; Yashaiya, Nadia Hezlin (2019)
This article identifies and examines factors important to the collaborative process. It does so by treating Malaysia’s performance and management delivery unit (PEMANDU) – which is an agent that played a central role in economic and government transformation programmes – as a prism from which to identify essential components of collaboration. By examining PEMANDU’s various initiatives together with descriptions of two cases on collaboration, the article concludes that facilitative leadership and one-of-a kind organizational design are necessary but not sufficient conditions for a successful collaborative-governance endeavor. Institutionalizing collaborative governance remains problematic. This is because even though collaborative governance is nested within the country’s larger development concerns, the issues of trust, legitimacy and regime change have made collaborative governance a still nascent tool for public-sector reform effort.